Studi Literatur: Analisis Kesulitan Belajar Matematika Siswa Sd Pada Materi Penjumlahan Dan Pengurangan Bilangan - Armilah Hinda Wati; Agustina Agustina; Fijriyati Fijriyati; Ujang Jamaludin; Sigit Setiawan (Jurnal Ilmiah Wahana Pendidikan, 2023)
In this study, a literature review method was employed to gather and analyze data relate to errors in learning mathematics, specifically in the topics of addition and subtraction at the elementary school level. Secondary data from journals, books, and relevant official documents were utilized. The study followed three main steps, which involved collecting relevant literature, integrating the findings of the literature review into a summary, and identifying debated issues within each literature source. The data analysis was conducted using the bibliography annotation method. The research findings indicated several factors that contribute to difficulties in learning mathematics, including misconceptions in subtraction operations involving the number zero, insufficient problem-solving skills among students, challenges in reading and writing, and difficulties in comprehending addition and subtraction procedures. Proposed solutions to address these learning difficulties include providing more concrete exercises, enhancing student understanding through repeated practice, and shifting the learning approach from concrete to abstract.